Biomarker profiling and integrating heterogeneous models for enhanced multi-grade breast cancer prognostication - Joshi, Rakesh Chandra; Srivastava, Pallavi; Mishra, Rashmi; Burget, Radim; Dutta, Malay Kishore (Computer methods and programs in biomedicine, 2024)
BACKGROUND: Breast cancer remains a leading cause of female mortality worldwide, exacerbated by limited awareness, inadequate screening resources, and treatment options. Accurate and early diagnosis is crucial for improving survival rates and effective treatment. OBJECTIVES: This study aims to develop an innovative artificial intelligence (AI) based model for predicting breast cancer and its various histopathological grades by integrating multiple biomarkers and subject age, thereby enhancing diagnostic accuracy and prognostication. METHODS: A novel ensemble-based machine learning (ML) framework has been introduced that integrates three distinct biomarkers-beta-human chorionic gonadotropin (β-hCG), Programmed Cell Death Ligand 1 (PD-L1), and alpha-fetoprotein (AFP)-alongside subject age. Hyperparameter optimization was performed using the Particle Swarm Optimization (PSO) algorithm, and minority oversampling techniques were employed to mitigate overfitting. The model's performance was validated through rigorous five-fold cross-validation. RESULTS: The proposed model demonstrated superior performance, achieving a 97.93% accuracy and a 98.06% F1-score on meticulously labeled test data across diverse age groups. Comparative analysis showed that the model outperforms state-of-the-art approaches, highlighting its robustness and generalizability. CONCLUSION: By providing a comprehensive analysis of multiple biomarkers and effectively predicting tumor grades, this study offers a significant advancement in breast cancer screening, particularly in regions with limited medical resources. The proposed framework has the potential to reduce breast cancer mortality rates and improve early intervention and personalized treatment strategies.
Keywords: dospělí; Ensemble learning; nádory prsu; Female; AI-based screening; Machine learning in healthcare; alpha-Fetoproteins; Adult; ženské pohlaví; strojové učení; lidé; umělá inteligence; Neoplasm Grading; Breast Neoplasms; Algorithms; prognóza; stupeň nádoru; nádorové biomarkery; Aged; alfa-fetoproteiny; Machine Learning; Breast cancer diagnosis; algoritmy; Prognosis; Biomarker-driven classification; Biomarkers, Tumor; lidé středního věku; senioři; Artificial Intelligence; Middle Aged; Multi-grade prediction; Humans